PENINGKATAN HASIL BELAJAR JARAK DALAM RUANG MELALUI PBL DAN GEOGEBRA PESERTA DIDIK KELAS XII SMA INSAN CENDEKIA MANDIRI BOARDING SCHOOL - Yulianto, Bintang Wiyono Bakti (CV Sintesia, 2025)
This research is a classroom action research that aims to determine the improvement of learning outcomes in distance in space material through PBL (Problem Based Learning) and the application of geogebra for XII graders of Senior High School Insan Cendekia Mandiri Boarding School that the number is 15 students. This research was conducted in 3 cycles with each cycle consists of 2 meetings. Data collection techniques were carried out using learning outcomes tests. Based on the results of the study, in the first cycle, the average student learning outcomes were 63 with low category. Meanwhile, in the second cycle the average student learning outcomes were 71 with high category and in the third cycle the average student learning outcomes were 85 with very high category. Thus, the learning outcomes of XII graders have increased through PBL and geogebra applications.